Hubungan Kejadian Kecacingan dengan Anemia Defisiensi Besi pada Anak-Anak Pengrajin Gerabah di Lombok Barat - Wibowo, Ruth Christina; Kurniawan, Yudhi; Triani, Eva (Faculty of Medicine Universitas Mataram, 2019)
Research Background: Helminthiasis, especially Soil Transmitted Helminths (STH), is a health problem globally. The high number of helminthiasis on children is caused by many factors, especially demographic factor. Helminthiasis leads to disorders of intake, intestine, absorption, and metabolism. Iron Deficiency Anemia (IDA) is one of disorders caused by helminthiasis. IDA itself could cause failure to thrive on children. This concerns research to know the relationship between helminthiasis and IDA on children of pottery craftsman in West Lombok, especially in SMPN 2 Kediri. Methods: This research exerted analytic descriptive research method and cross sectional approaches. The research data was employed through questionnaire that shared to the students. The subjects of research were taken from 50 students of 7th and 8th class of SMPN 2 Kediri, West Lombok. The data analysis employed Chi-Square statistic test and SPSS 23,0. Research Goals: This research goals showed that the students who were positively infected by intestinal worm 17 students (34%). Worms infecting the students are Trichuris trichiura in 10 students (58,82%), followed by Enterobius vermicularis, Ascaris lumbricoides, Ancylostoma duodenale, anạ mix of Trichuris trichiura and Ascaris lumbricoides. Factors that is related with this helminthiasis are wearing footwear habit with P value <0,05 and biting nails habit with P value <0,05. Four students (8%) are suffering IDA. This helminthiasis has a meaningful relationship with IDA with P value <0,05. Conclusion: It was indicated interrelation between the incident of intestinal worm and iron deficiency anaemia in SMPN 2 Kediri, West Lombok.